Neuropsychological tests and driving in dementia: a review of the recent literature - Silva,Marcia Thereza (2009)
INTRODUCTION: Neuropsychological tests measure several aspects of cognition and are useful to evaluate elderly drivers with cognitive impairment. However, there is no consensus on a standard battery of tests that could accurately predict safe driving. OBJECTIVE: The aim of this study is to review specific neuropsychological measures that may be useful to predict driving competence of demented individuals. METHOD: To address neuropsychologicaltests used for dementia and the ability to drive, the authors searched for the keywords dementia, Alzheimer's, drive, driver, drivers, driving, tests, neuropsychological, and assessment, in Medline, PubMed, ISI and SciELO databases seeking articles from 2000 to 2008. RESUTLS: From 131 articles, 27 met the inclusion criteria. Porteus Maze, Clock drawing, Trail B, UFOV and NAB Tests were found to be the most relevant neuropsychological measures for the evaluation of fitness to drive. CONCLUSION: Porteus Maze, Clock Drawing, Trail B, UFOV and NAB tests highlight visuospatial attention demands and/ or executive function. Those and other visuospatial and executive measures may be useful to predict driving competence of demented individuals.